Teaching Function at University - Alma Elena Figueroa Rubalcava; María del Carmen Gilio Medina; Victoria Eugenia Gutiérrez Marfileño (Universidad Autónoma de Baja California, 2008)
A peremptory change in education and the higher education at universities is occurriyng. Since 60´s to date theoretical issues on the role of education are continuously on modification more rapidly than the teaching and learning practices that need more time to be realized. In this paper is presented a broad scope of main national and international organizations that propose, promote and systematize those educational changes since a half century ago and specially, those that impact the formation tendency based on competences. On other side, and not pretending be exhaustive, in this paper is highlighted a list of educational competences that teachers need to develop if they pretend to realize their teaching functions with high quality standards, mainly those related with velocity involvement as curriculum constructor.